Characterization of a New Virulent Phage (MLC-A) of Lactobacillus paracasei - Capra, María Luján (2006)
A new virulent bacteriophage (MLC-A) was recently isolated in Argentina from a probiotic dairy product containing a strain of Lactobacillus paracasei. Observation of the lysate with an electron microscope revealed bacteriophage particles with an icosahedral capsid of 57 ± 2 nm; with a collar and a noncontractile tail of 156 ± 3 nm terminating with a baseplate to which a tail fiber was attached. Therefore, phage MLC-A belongs to the Siphoviridae family. This phage was able to survive the pasteurization process and was resistant to alcohols and sodium hypochlorite (400 mg/kg). Only peracetic acid could inactivate high-titer suspensions of phages in a short time. The maximum rates of phage adsorption to its host cells were obtained at 30°C with a pH between 5 and 7, and in the presence of calcium or magnesium ions. The host range of phage MLC-A encompassed L. paracasei and Lactobacillus casei strains, but it was not able to  nfect Lactobacillus rhamnosus or Lactobacillus gasseri strains. One-step growth kinetics of its lyticdevelopment revealed latent and burst periods of 30 and 135 min, respectively, with a burst size of about 69 ± 4 plaque-forming units per infected cell. Phage MLC-A had a distinctive restriction profile when compared with the 2 well-studied Lactobacillus phages, PL-1 and J-1. The genome size of the MLC-A phage was estimated to be approximately 37 kb. This study presents the description of the first phage specific for L. paracasei isolated in Argentina. The isolation of phage MLC-A indicates that, beside lactic acid bacteria starters, MLC-A indicates that, beside lactic acid bacteria starters, probiotic cultures can also be sensitive to virulent phages in industrial processes.